ChemInform Abstract: 1, 4‐Addition of an Aryllithium Reagent to Diethyl Ketomalonate. Scalable Synthesis of Ethyl 1‐(Hydroxymethyl)‐1, 3‐dihydroisobenzofuran‐1‐carboxylate. Issue 1 (3rd January 2013) - Rocke, Benjamin N.; Conn, Edward L.; Eisenbeis, Shane A.; Ruggeri, Roger B.
Abstract The title compound (IV) is prepared on a large scale.